The Future of the European Economy Part 2 - Van Rompuy, Herman (Institutional Knowledge at Singapore Management University, 2014)
This is the second of a two-part podcast featuring a dialogue session with His Excellency Herman Van Rompuy, President of the European Council, who was in SMU on 17 November 2014 as the 17th speaker of the SMU Presidential Distinguished Lecturer Series. In a wide-ranging discussion moderated by SMU President, Professor Arnoud De Meyer, His Excellency Van Rompuy shared his comments on topics such as the G20 Leaders’ Summit 2014, economic reforms in Europe, and the defining moments of his Presidency.